Menstrual Hygiene Management—Knowledge, Attitudes, and Practices Among Female College Students in Bhutan - Tshomo, Tashi; Gurung, Mongal Singh; Shah, Safieh; Gil-Cuesta, Julita; Maes, Peter; Wangdi, Rinchen; Tobden, Jamba (Frontiers in Reproductive Health, 2021)
Background: Girls and women face substantial menstrual hygiene management (MHM) challenges in low- and middle-income countries. These challenges are related to inadequate knowledge and insufficient water, sanitation, and hygiene (WASH) facilities. Currently, the literature on MHM among college-attending women in Bhutan is scarce. We aimed to explore the knowledge, attitudes, and practices (KAP) of female college students from all the 10 government colleges of Bhutan, documenting the conditions of available MHM facilities, from August to September 2018. Methods: A cross-sectional KAP survey was conducted with a random sample of female students from all years and a random sample of MHM facilities at each college and hostel. A questionnaire was adapted from a similar study conducted with school students in Bhutan. Socio-demographics, overall KAP findings, and differences in KAP between first and final year students were analyzed; college and hostel toilets were self-reported and directly observed. Results: In the survey, 1,010 participants completed the self-administered questionnaire. The comprehensive knowledge of menstruation was found to be low (35.5%) among participants. Half of the participants (50.3%) reported their mother as the source of information, and 35.1% of the participants agreed that women should not enter a shrine during menstruation. It was also reported that approximately 4% of median monthly pocket money was spent on the absorbents, and 96.9% of absorbents were wrapped before disposal. Half of the participants (55.1%) reported that their daily activities were affected due to menstruation, and 24.2% of the female students missed college due to dysmenorrhea. One-fifth of the participants (21.3%) reported unavailability of water in college, 80.1% of the participants reported absence of soap for hand washing, and 24.1% described no bins for disposal. The participants also reported that in 33.7% of hostel toilets, the door locks were missing. The direct observations also had similar findings. Conclusions: Female students living in hostels during college years lose considerable resources during their formative years of learning, such as time, energy, and money, due to issues of menstruation management. Although the overall understanding of menstruation was low, the MHM practices of our participants scored highly, and the vast majority of them asked for a platform to discuss menstruation. Despite some agreement with menstrual taboos (e.g., visiting shrine), only 5.1% of the participants were uncomfortable conversing about MHM. Improved public health knowledge, psychosocial/medical support, and WASH infrastructure with freely available menstrual products could lead to more effective MHM practices among female college students.